2015
DOI: 10.4172/2157-7099.1000360
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of the Drugs used for the Treatment of Thalassemia

Abstract: Thalassemia is one of the most prevalent inherited blood disorders all over the world. There are some specific hematologic tests and molecular genetic techniques known for diagnosis of thalassemia. Nowadays, various types of drugs are used for the treatment of thalassemia. Hydroxyurea, Hydroxycarbamide, Deferiprone, Deferisirox, Butyrate and its derivatives are some of the most common and well known drugs which are used for increasing the HbF percentage and iron chelation. Pharmacogenomics is the branch of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Butyrates are a class of histone deacetylase (HDAC) inhibitors demonstrated to be able to increase γ-globin gene expression and HbF content in erythroid cells from βthalassemic and SCD patients [171][172][173]. It has been reported that at least 25% of the patients affected by hemoglobinopathies do not respond to treatment with butyrates [174,175]. However, despite the fact that butyrates have been proposed as good candidate drugs for pharmacogenomic studies [174], few reports have been published on this issue.…”
Section: Butyrate and Butyrate Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrates are a class of histone deacetylase (HDAC) inhibitors demonstrated to be able to increase γ-globin gene expression and HbF content in erythroid cells from βthalassemic and SCD patients [171][172][173]. It has been reported that at least 25% of the patients affected by hemoglobinopathies do not respond to treatment with butyrates [174,175]. However, despite the fact that butyrates have been proposed as good candidate drugs for pharmacogenomic studies [174], few reports have been published on this issue.…”
Section: Butyrate and Butyrate Analoguesmentioning
confidence: 99%
“…It has been reported that at least 25% of the patients affected by hemoglobinopathies do not respond to treatment with butyrates [174,175]. However, despite the fact that butyrates have been proposed as good candidate drugs for pharmacogenomic studies [174], few reports have been published on this issue. An interesting study is based on the observation that patients who are unresponsive to HU treatment can be treated with sodium butyrate containing microRNAs to induce HbF synthesis [174,176].…”
Section: Butyrate and Butyrate Analoguesmentioning
confidence: 99%
“…The effectiveness of HU administration was reported only in certain groups of patients with β thalassemia major, because it requires selecting groups of responders and nonresponders. Several studies have even reported failure of HU therapy in patients with β-thalassemia major (Dreuzy et al, 2016;Panja & Basu, 2015;Thein, 2005).…”
Section: Introductionmentioning
confidence: 99%